PRONUNCIATION CHALLENGES FACED BY UZBEK EFL LEARNERS: PRONUNCIATION CHALLENGES FACED BY UZBEK EFL LEARNERS - Behruzkhon Yuldoshev Behzod ugli (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
This article explores the major pronunciation difficulties encountered by Uzbek learners of English as a Foreign Language (EFL). It examines how linguistic, phonetic, and sociocultural factors influence learners’ ability to produce accurate English sounds. The study also highlights the role of native language interference, insufficient phonetic training, and limited exposure to authentic English speech. Recommendations are provided for teachers to design pronunciation-focused instruction and integrate phonetic awareness into communicative learning environments.